A rare case of gastric perforation by a 5-year-old Intra-gastric Balloon in situ: Case report and review of literature. (2020) - Vinod, Vijay Chander; Younis, Muhammad Umar; Mubarik, Humera; Rivas, Homero
Highlights: 5-Year-old Intra-gastric Balloon. Gastric perforation. Acute abdomen. Bariatric surgery. Abstract: Introduction: Insertion of an Intra gastric Balloon (IGB) has widely been used as a minimally invasive procedure for the treatment of obesity. Gastric balloons are usually inserted for a period of six months only. They have a high safety profile and one of their rare, reported, serious complications include gastric or esophageal perforation, which are usually early and require immediate operative management. Presentation of case: We report a 26-year-old lady who presented to the ED with signs and symptoms of acute abdomen and five-year history of endoscopic placement of Intra-gastric Balloon. Emergent endoscopic removal of the balloon revealed a large pressure ulcer at gastric incisura with central necrosis. Laparoscopy confirmed gastric perforation along lesser curvature with extensive soilage of peritoneal cavity. Extensive irrigation and drainage and Graham omental patch repair were carried out laparoscopically, and the perforation sealed satisfactorily. She recovered well from surgery and within days she was tolerating a diet. Broad spectrum IV antibiotics were given for 10 days. Discussion: Gastric perforation is a rare complication reported in 0.1% of patients undergoing IGB insertion. It can ensue as early as days after placement or late at weeks to months. In our review of literature, we found the maximum time frame in which a patient presented with an IGB induced gastric perforation was at 22 months. This makes our case unique as the patient was able to tolerate it for 5 years (60 months) before presenting to the emergency with this sinister complication. Conclusion: Very late Gastric perforations in patients with IGB placement are rare. An upper gastrointestinal endoscopy should be arranged as soon as possible to remove the balloon and assess the stomach visualize the perforation followed by a laparoscopic approach to repair the defect if expertise is available.